Decolonizing epistemologies : Latina/o theology and philosophy - Isasi-Díaz, Ada María; Mendieta, Eduardo (Transdisciplinary theological colloquia., 2012)
This anthology gathers the work of three generations of Latina/o theologians and philosopher who have taken up the task of transforming their respective disciplines from the standpoint of liberation and what has been called the "decolonial turn" in social theory, theology, and philosophy. It articulates a new point of departure for the self-understanding of not simply Latina/os, but also US citizens in this new age of post-colonialism and globalisation.